Beneficial roles of feed additives as immunostimulants in aquaculture: a review - Mahmoud A.O. Dawood; Shunsuke Koshio; Maria Ángeles Esteban (Reviews in Aquaculture, 2018)
The use of antibiotics in the aquafeeds to mitigate infectious diseases or to boost growth performance is commonly practiced. Recently, the prophylactic use of antibiotics and chemotherapies have been criticized which eventually led to their ban in aquaculture by law on many countries. In view of the current restrictions on antibiotic use, there is a critical need to evaluate other possible alternatives. One potential substitute for antibiotics in aquafeeds is the use of functional feed additives. The present review is a comprehensive and an updated compilation of the available works on different feed additives, their examples, modes of action and useful applications for improving aquafeeds. It highlights several functional feed additives including probiotics, prebiotics, synbiotics, immunostimulants, organic acids, nucleotides and medicinal herbs. Apart from boosting aquafeeds and safeguarding general health of aquatic animals, some of these substances have been found to possess beneficial immunostimulant and anti‐stress relieving properties. Furthermore, the use of these natural substances increases the consumer confidence of farmed fish. Due care has been taken to cover the on‐going trends and recent advances with a perspective vision and their holistic usages and beneficial applications in aquatic animals’ systems. The current study also shed light regarding the management and production aspects of aquatic animals which will enlighten farmers and producers for better economic growth.